DETERMINAN KEBERHASILAN USAHA PADA SENTRA KERAJINAN GERABAH - Anandita Zulia Putri; Idha Ayu Isnaini; Ningrum Pramudiati (UNIB Press, 2023)
The purpose of this study was to determine whether entrepreneurial characteristics, use of accounting information and accounting attitudes had an effect on business success. This type of research method is quantitative research. This study uses primary data in the form of a questionnaire that is distributed directly to the owners of MSMEs. The population of this research is all pottery and leather handicraft centers in Bantul Regency, the sampling technique uses purposive sampling technique with the criteria of length of business, initial capital, MSMEs that have been registered in the Bantul Regency Cooperatives and SME Service and MSMEs that have recorded their business, the sample obtained as many as 99 respondents. The data analysis technique used multiple linear regression analysis with the help of the SPSS v.25 tool. The results of this study state that partially and simultaneously entrepreneurial characteristics, use of accounting information and accounting attitudes have an effect on business success.